UCP2 regulates energy metabolism and differentiation potential of human pluripotent stem cells. (15th April 2016) - Zhang, Jin; Khvorostov, Ivan; Hong, Jason S; Oktay, Yavuz; Vergnes, Laurent; Nuebel, Esther; Wahjudi, Paulin N; Setoguchi, Kiyoko; Wang, Geng; Do, Anna; Jung, Hea‐Jin; McCaffery, J Michael; et al.
Abstract :